PENGGUNAAN TEPUNG MOCAF (Modified cassava flour) DENGAN PERSENTASE BERBEDA MEMPENGARUHI KUALITAS BOLU KUKUS - Zaki, Muhammad; Devi, Mazarina; Hidayati, Laili (Journal of Food Technology and Agroindustry, 2024)
Mocaf flour is fermented cassava flour so it contains high nutrients. The purpose of this study was to analyze the effect of mocaf flour percentage substitution in steamed cakes with natural dyes of broccoli powder on physical, chemical and hedonic properties. The experimental research method was a completely randomized design with 3 substitution treatments of mocaf flour percentages of 50%, 60% and 70%, 2% broccoli leaf powder natural dye twice repetition. Data were analyzed by One-Way ANOVA test and DMRT with a significance of 0.05. The results showed that there was a significant effect on the chemical, physical and hedonic properties of steamed sponge mocaf flour 50%, 60% and 70% natural dyes 2% broccoli leaf powder. The highest levels of protein, swelling and pores at 50% were 7.62%, 399.275% and 79.5 cm2. The highest levels of carbohydrates, crude fiber and antioxidant capacity at 70% were 39.62%, 0.99% and 20.32%. The most preferred percentage of the hedonic test was steamed sponge cake with 50% Mocaf flour substitution in terms of color, taste and texture.